2018
DOI: 10.1016/j.scriptamat.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Atomic worlds: Current state and future of atom probe tomography in geoscience

Abstract: Atom Probe Microscopy (APM) is rapidly finding new applications within the geosciences. Historically connected with materials science and semiconductor device applications, recent years have seen an exciting trend as APM has proved a useful tool for nanoscale geochemistry, as it offers unique capabilities when compared with the current suite of conventional geoanalytical techniques. The ability to characterize 3D nanoscale chemistry with isotopic sensitivity, and correlate these results with other analytical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 90 publications
(90 reference statements)
1
28
0
Order By: Relevance
“…Valley et al [64] proposed FIB and APT techniques as a valuable tool for studying a 4.4-Gyr-old Hadean zircon, as shown in Figure 5. It was found that isolated nanoclusters are enriched in incompatible elements including radiogenic Pb with an unusually high 207 Pb/ 206 Pb ratio, though the average bulk value of 207 Pb/ 206 Pb is in good agreement with SIMS data at the micron scale [58,64]. The accurate U-Pb isotopic analysis of nanoscale domains from this work opens up a new era of nanogeochronology [58,59].…”
Section: Applications Of the Fib-sem Systemsupporting
confidence: 57%
See 2 more Smart Citations
“…Valley et al [64] proposed FIB and APT techniques as a valuable tool for studying a 4.4-Gyr-old Hadean zircon, as shown in Figure 5. It was found that isolated nanoclusters are enriched in incompatible elements including radiogenic Pb with an unusually high 207 Pb/ 206 Pb ratio, though the average bulk value of 207 Pb/ 206 Pb is in good agreement with SIMS data at the micron scale [58,64]. The accurate U-Pb isotopic analysis of nanoscale domains from this work opens up a new era of nanogeochronology [58,59].…”
Section: Applications Of the Fib-sem Systemsupporting
confidence: 57%
“…It was found that isolated nanoclusters are enriched in incompatible elements including radiogenic Pb with an unusually high 207 Pb/ 206 Pb ratio, though the average bulk value of 207 Pb/ 206 Pb is in good agreement with SIMS data at the micron scale [58,64]. The accurate U-Pb isotopic analysis of nanoscale domains from this work opens up a new era of nanogeochronology [58,59]. In addition, FIB and APT techniques have been also used for the study of deformation induced trace element migration and the nanoscale gold clusters in arsenopyrite [58,65,66].…”
Section: Applications Of the Fib-sem Systemmentioning
confidence: 56%
See 1 more Smart Citation
“…[339][340][341] The FIB has allowed to precisely target the preparation of specimens for APT [342,343] that enabled to avoid the trial and error approach of the previous decades. Laser-pulsing lifted the requirement that the specimen must be a good electrical conductor to be analyzed by APT, [319,[344][345][346][347] but also increased the yield significantly. [348] The use of FIB allows to first select a microstructural feature of interest by using the scanning electron microscope, including using advanced techniques such as electron backscattered diffraction [189] or electron channeling contrast imaging for instance.…”
Section: B Atom Probe Tomography For the Investigation Of Advanced Smentioning
confidence: 99%
“…Detailed mass spectra with high resolution of peaks, identified in Table 2, can be found in Supplementary Figures S1-S4. A challenging aspect of using atom probe tomography for the analysis of geological materials is the complexity of mass spectra and the possibility of peak overlaps [14]. Such complexity is effectively multiplied if organic species are analyzed in conjunction with minerals [9,10,12].…”
Section: Apt Datamentioning
confidence: 99%